EMAST Instability and CHEK2 Promoter Analysis in Colorectal Cancer - S Rezapour; M Meuth (Iranian Journal of Public Health, 2005)
Colorectal cancer is the third leading cause of cancer death with an estimated 430,000 death per year worldwide. This cancer is a common disease that about 95% is sporadic. Accumulation of somatic mutations in a cell is the basis of sporadic colon cancer. Mutations of different classes of genes have been described in colon cancer etiology such as oncogenes and suppressor genes. Primary screening using single strand conformation polymorphism (SSCP) has been carried out for 132 colorectal cancer samples. Samples showing altered mobility on SSCP gels were sequenced. PCR-SSCP and Sequencing of the CHEK2 exons in DNA tumours revealed a polymorphism at nucleotide 252 in codon 84 and CHEK2 alteration in exon 11. These included missense mutations that altered amino acids Tyrosine to Histidine and Glutanic acid to Lysine in kinase domain of the CHEK2 protein. In addition, to find relationship between expression of CHEK2 protein and changes in CHEK2 gene in colorectal cancer, immunohistochemistry analysis was performed. Tumour samples, which contain the CHEK2 gene alterations, showed negative to very low levels of CHEK2 protein. We used methylation specific PCR techniques (MSP) to determine the methylation status of the CHEK2 promoter in colorectal cancer. We found that CpG rich regions of the CHEK2 gene promoter is methylated in random cases with negative to low level protein expression. CHEK2 alterations are not common in sporadic colorectal cancer but can be detected in about 6% of cases and methylation of CHEK2 promoter sequences was also detected approximately in 10% of the cases. EMAST (Elevated Microsatellite Alterations at Selected Tetranucleotides) that is a distinct subtype of microsatellite instability and can be a useful marker for the early detection of cancer. DNAs from tumours and normal mucosae were polymerase chain reaction (PCR) amplified at six tetranucleotide repeat microsatellite (EMAST) loci. EMAST was observed at least in one of six markers in 69.7% of colorectal tumours. All EMAST positive tumours were of advanced stage. Also 11.4% of cases demonstrated a loss of heterozygosity (LOH) with at least 1 of 6 microsatellite markers.